Renewing Universities in Our Climate Emergency: Stewarding System Change and Transformation - Fazey, Ioan; Hughes, Claire; Schäpke, Niko A.; Leicester, Graham; Eyre, Lee; Goldstein, Bruce Evan; Hodgson, Anthony; Mason-Jones, Amanda J.; Moser, Susanne C.; Sharpe, Bill; Reed, Mark S. (Frontiers in Sustainability, 2021)
This paper outlines climate emergencies facing universities and, by drawing on research on system transition, provides insights about how change to overcome the challenges might be stewarded. Climate change brings three interconnected and urgent emergencies for universities: (1) Manifest emergencies such as risks to operations and business models; (2) Conceptual emergencies that arise because assumptions, ideologies, systems and structures cannot match the scale of the manifest challenges; and (3) Existential emergencies where current identities and sense of purpose are incapable of supporting the changes needed to overcome the conceptual challenges. To be viable leaders in the world, universities will need to renew their commitments to serving the public good, be dedicated to an unwavering challenge-orientation, create post-disciplinary structures, and be the change one seeks to see in the world. Importantly, universities will need to overcome the emergencies on the inside if they are to help society address the scale of the challenges on the outside, to which both universities and human capacity are seriously cognitively and emotionally ill-prepared. Fortunately, new insights from research on system transition provide helpful advice on how to steward transformational change. This work highlights that successful transformation requires strong adherence to transformational intent and, in the case of universities, working with all three emergencies simultaneously. Successful transformation will also require harnessing opportunities to disrupt the status quo; supporting an interplay of different forms of management and orientations to the future; developing appropriate infrastructure to support transformation; and rapidly accelerating the development of capacities for transformational change. By actively developing capacities for transformation on the inside universities will then be in a much better position to help and lead others beyond the halls of the academy.